(untitled) (Journal SCIENCEVOLUTION, 2024)
This text is presented as a review of the book ‘La Evaluación de la Calidad Educativa en las Instituciones de Educación Superior Públicas de México: Un Estudio de Caso con Enfoque de Aseguramiento de la Calidad y Rendición de Cuentas’, authored by Miguel Ángel Medina-Romero. The book was published in 2023, following an academic review process by an editorial committee and a double-blind peer review by the Brazilian publishing house Atena Editora. This book is 464 pages long, the ISBN is 978-65-258-1972-3 and DOI is https://doi.org/10.22533/at.ed.723231310